A Comparative Study of a Three Rotor and a Single Rotor 5 MW Wind Turbine Based on Economic and Structural Considerations. Issue 6 (December 2014) - Manwell, James F.; McGowan, Jon G.; Brena, Sergio; Verma, Preeti
Wind turbines with more than one rotor on a single support structure have been topics of interest for at least a hundred years. In this paper we assess the potential of the multi-rotor concept through a comparison of a three rotor, single tower turbine with a total rated capacity of 5 MW with a conventional, single rotor turbine with the same rated output. Except for the number of rotors, the turbines are in all other ways as similar as possible. The comparison first involves estimating the weights and costs of the two turbines. The three rotor turbine also requires a distinct rotor nacelle assembly support structure (RNASS) which is not required in a conventional turbine. A plausible design for such a structure is developed and analyzed. The weight and cost of that structure is estimated as well. Those are used to estimate the total weight and total cost of the part of the turbine which would correspond to the rotor nacelle assembly of the single rotor turbine. The results of this study show that the weight of the three rotor turbine, including the RNASS is likely to be comparable to or higher than that of a single rotor turbine, but that the cost of the three rotor turbine may well be less. The reason for the lower cost is in effect the substitution of less expensive material (structural steel) for more expensive material (blades and drive train components). The overall conclusion is that multiple rotor turbines look most attractive for those situations where a turbine with a very large rated capacity is for some reason desirable. The most obvious situation where this may the case is offshore, where the cost of support structures is very high.